2021
DOI: 10.1167/iovs.62.4.16
|View full text |Cite
|
Sign up to set email alerts
|

IL-36α Exerts Proinflammatory Effects in Aspergillus fumigatus Keratitis of Mice Through the Pathway of IL-36α/IL-36R/NF-κB

Abstract: IL-36α exerts proinflammatory effects in Aspergillus fumigatus keratitis of mice through the pathway of IL-36α/IL-36R/NF-κB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
(29 reference statements)
0
8
0
Order By: Relevance
“… 33 Recent evidence suggests that the NF-κB pathway is activated in murine Aspergillus fumigatus keratitis. 15 , 34 However, the upstream regulators of the NF-κB pathway in FK remain obscure. Notably, our study found that the expression of inflammatory factors was elevated and that the NF-κB pathway was activated in FK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 33 Recent evidence suggests that the NF-κB pathway is activated in murine Aspergillus fumigatus keratitis. 15 , 34 However, the upstream regulators of the NF-κB pathway in FK remain obscure. Notably, our study found that the expression of inflammatory factors was elevated and that the NF-κB pathway was activated in FK.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear factor kappa B (NF-κB) signaling pathway is typically involved in inflammatory response and plays an indispensable role in the physiological and pathological mechanisms of infectious keratitis. 14 , 15 However, the upstream regulator of the NF-κB signaling pathway in FK remains elusive. Recent research has demonstrated that METTL3 can modulate the inflammatory response in macrophages via the NF-κB signaling pathway in rheumatoid arthritis.…”
mentioning
confidence: 99%
“…All the experiments were repeated three times. 48 MPO assay. To determine the activity of polymorphonuclear neutrophils, corneas were harvested at 3 days p.i.…”
Section: Assessment Of the Antifungal Efficiency Of Ocs In Vitromentioning
confidence: 99%
“…The inflammatory response can be initiated by macrophages via the release of proinflammatory cytokines. Therefore, macrophages can phagocytose and kill specific pathogens [ 54 ]. The phagocytosis of macrophages can be adjusted by miRNAs to moderate the clearance of the pathogen.…”
Section: Introductionmentioning
confidence: 99%